STRATEGI KEPALA MADRASAH DALAM PENGORGANISASIAN LAYANAN PENDIDIKAN DI MIN 16 ACEH BARAT - Iqbal, Muhammad; Rissa, Rahma (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
The school head's strategy is an important factor in determining the success of improving quality in the school. These include regulating how to organize work specialization, delegation of authority, and chain of command. This research aims to determine the strategy of school heads in organizing work specialization, organizing delegation of authority, and organizing the chain of command at MIN 16 West Aceh. To achieve this goal, this research uses a qualitative approach with descriptive methods with data collection techniques in the form of observation, interviews and documentation. The subjects in this research were the head of the school, deputy head of the school, head of administration, head of library, homeroom teacher and teacher at MIN 16 West Aceh. The results of the research show that: (1) The school head's strategy in organizing work specialization is by paying attention to diploma qualifications and placing people to carry out tasks according to their expertise, by dividing work among school personnel in the form of dividing tasks and responsibilities according to their teaching abilities. with an education diploma, (2) The school head's strategy in organizing the delegation of authority is carried out with the initial step of deliberation with teachers and school employees to discuss the work that will be delegated to school personnel. Then determine the results of the deliberation in a Decree, and supervise the performance of teachers and employees. (3) The school head's strategy in organizing the chain of command by paying attention to the organizational structure and work control of all school apparatus. The chain of command in the organizational structure of MIN 16 West Aceh is led by the head of the school assisted by the deputy head of the school for other sections such as coordinating with the deputy head of curriculum, student affairs and community relations. Then there is the treasurer, head of administration and administrative staff assisted by the operator. Next there are homeroom teachers and a board of study teachers and security guards.